The evaluation of the effects of ESG scores on financial markets - Michele Costa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2023)
We aim to explore the interplay between ESG scores and assets characteristics, specifically focusing on volatility. We classify stocks on the basis of both high/low ESG and high/low ESG momentum and we evaluate ESG effects by measuring the distance between the 2 group distributions. The analysis of stocks within the STOXX Europe 600 Index from 2017 to 2022 suggests that companies with higher ESG tend to exhibit lower volatility. However, we haven't observed a similar trend when examining ESG momentum. Furthermore, our findings enable us to highlight and compare the effects associated with the COVID pandemic and the conflict in Ukraine.
Keywords: G11; C40; Q56; 330; Sustainable finance; ESG; Stock market risk; Volatility